Analysis of the evolution of aerospace manufacturing ecosystems - Luna Andrade, Jose Junior (Cranfield University, 2020)
The aerospace manufacturing industry is predicted to continue growing. Understanding its evolution is thus essential to prepare optimal conditions to nurture its growth. This research aims to help the growth of emerging aerospace ecosystems by identifying evolution patterns and categorising key enablers that have encouraged the growth of developed ones. The term aerospace ecosystem is used to embrace all the business activities and infrastructure that are related to the entire aerospace’s supply chain in a specific country. Inspired by studies that have successfully combined economics and network science, in this research, bipartite country-product networks are developed based on trade data over 25 years. The United Kingdom (UK), the United States of America, France, Germany, Canada and Brazil’s are first analysed as evidence suggests that their aerospace ecosystems are within the most developed in the world. Then, China and Mexico’s networks are analysed and compared with developed ones, as these countries have evidenced emergent aerospace ecosystems. Results reveal that developed ecosystems tend to become more analogous, as countries lean towards having a revealed comparative advantage (RCA) in the same group of products. Further analysis shows that manufactured products have a stronger correlation to an aerospace ecosystem than primary products; and in particular, the automotive sector shows the highest correlation with positive aerospace sector evolution. Key enablers related to the growth of the UK and Mexico’s aerospace ecosystems are identified and categorised using interpretive structural modelling (ISM) and cross-impact matrix multiplication applied to classification (MICMAC) methodologies. Results evidence relevant differences in the categorisation of key enablers among a developed and emergent aerospace ecosystems. On the other hand, it was identified that geopolitical factors and the automotive ecosystem are underpinning enablers for both aerospace ecosystem’s evolution. The final aim is that results of this research could be implemented on emerging aerospace ecosystems by emulating the patterns and key enablers that have characterised the evolution of developed aerospace ecosystems.
Keywords: Network science; bipartite networks; nestedness; comparative advantage; interpretive structural modelling (ISM); cross-impact matrix multiplication applied to classification (MICMAC); aerospace manufacturing; industrial ecosystem